Efektivitas Model Pembelajaran Kooperatif Tipe Numbered Heads Together terhadap Hasil Belajar Matematika Siswa Sekolah Dasar - Firdaus, Firdaus; Asriadi, Asriadi; Muallim, Muallim (Universitas Pahlawan Tuanku Tambusai, 2024)
This study looks at how well the NHT cooperative learning method helps elementary school students do better in math. The study is inspired by noticing that students don't participate much and don’t learn well in math. Classes are often boring and mostly focus on the teacher. This study uses a simple method where a single group is tested before and after an experiment. It includes 22 sixth-grade students from UPT SD Negeri 41 Mallari. Information was gathered using tests to check learning progress (before and after lessons), student feedback forms, and observation sheets for how lessons were carried out. We analyzed the data using two main approaches: looking at it in a straightforward way and making inferences. This included checking for normal distribution, testing for consistency across groups, and testing our hypotheses with a Paired Samples Test. The study is expected to show that using the NHT cooperative learning model helps students learn math better and makes them more involved in the learning process.